Personification Language Style in The Poem Created by ChatGPT - Muhamad Saiful Mukminin; Libra Dui Putra; Ahmad Abdul Muhhit; Amon Bernabas Tenis (Journal of Education and Contemporary Linguistics, 2024)
The present research aims to analyze the use of personification in poems generated by ChatGPT. A qualitative descriptive method is employed to examine the use of personification in the poems produced by this language model. The data used in the study consists of poems generated by the ChatGPT platform. Data collection techniques include observation and note-taking by providing the prompt “create a poem!” to ChatGPT. The data analysis is conducted in three stages: data reduction, data presentation, and conclusion drawing. In the data reduction stage, parts of the poems containing personification are identified, focusing on the attribution of human characteristics to inanimate objects or abstract concepts. In the data presentation stage, the poems containing personification are described and explained, accompanied by concrete examples and contextual explanations of their usage. In the final stage, conclusions are drawn based on the analysis. The results of the study show that out of the ten poems analyzed, 28 cases of abstract personification and 33 cases of concrete personification were found. The poem titled Whispering Love stands out for its use of abstract personification, while the poem Harmony of Nature predominantly uses concrete personification. Personification in ChatGPT-generated poems enhances both aesthetic and emotional quality and helps make abstract concepts more comprehensible to readers.